PERANCANGAN SISTEM INFORMASI PENYEWAANEQUIPMENT EVENT BERBASIS WEBSITE PADAQUPRODUCTION QUPRO INDONESIA - Zulfikar Jafar Shidiq, (2021)
Quproduction is one of the providers of equipment rental services for the needs of events such as music concerts, seminars, and others. The system that runs like this is considered less effective because there are still obstacles experienced by the service provider. Based on this, it is proposed to make a web-based equipment rental system. The method used in this research is the Waterfall method. System requirements analysis was carried out using the PIECES method, and the proposal system design used the UML method. Based on the results of the system development, a new rental information system based on a website can be created where there are several features to use from both the tenant and the admin. The main features contained in this application are tenants can make rentals directly in the application and admins can manage goods that can be rented in this application.